SOSIOLEK KOMUNITAS WARIA DI KOTA PONTIANAK MENGGUNAKAN PENDEKATAN SOSIOLINGUISTIK - Sari, Nila; Syahrani, Agus; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractSosiolek is variation of the language with regard to status, groups, socialclasses and speakers. Sosiolek is variation related to the science of Sociolinguistics. The researchers chose sosiolek in research to describe the inventory, variation, and language function in the community of transvestites in the city of Pontianak. Special issue of how the inventory of vocabulary in the language environment of the union of transvestites Pontianak town (Perwapon), how variation transsexual union environment in Pontianak town (Perwapon), how language functions at union City's Transvestites Pontianak (Perwapon).This research uses descriptive method, a form of qualitative research, and sociolinguistic approaches. The source of the data in this study was the informant (transvestites), and its data are words used in everyday conversation transvestites. The technique of data collection conducted in this research is the technique of fishing rods, and record and note. The data analysis undertaken in this study, the researchers did a transcript of all the vocabulary.Â Keywords: Informant transsexual language and sosiolek.